Why Development Failed? Facts and Analysis of Development Failure in Sumenep - Hidayaturrahman, Mohammad; Hidayat, Imam; Wibisono, Aryo (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2020)
This research was conducted to find a complete picture as well as to study comprehensively on the facts and factors causing the failure of development using the regional budget in Sumenep regency, East Java. During this time, national development which is supported by the efforts of regional governments in maximizing the potential of the regional budget is an important foundation in achieving public welfare. This research implemented an explanative qualitative method, with a single case study in Sumenep Regency that has an area consisting of mainland and islands, so it required large development funding. Data collection was done by in-depth interviews, direct observation, and online document search. This study also uses a quantitative method that measures the effect of the regional budget on development. From the research, it was found that with a large number of development funds from the regional budget there were still a lot of stagnant, abandoned physical developments that were not utilized. The aftermath was that the realized development fund could not overcome poverty, unemployment, and could not increase the income and welfare of residents in Sumenep Regency. Several factors were causing the failure of development in Sumenep Regency which was described comprehensively throughout the study.